ANALISIS HARGA POKOK PRODUKSI, NILAI TAMBAH DAN PENDAPATAN AGROINDUSTRI TAHU SMS DI JAGABAYA KOTA BANDAR LAMPUNG - Sianturi, Sulastri; Zakaria, Wan Abbas; Riantini, Maya (Lampung University, 2023)
This study aims to analyze cost of goods manufactured, added value, and tofu agro-industry income. This research uses a case study method. Therefore, it was chosen purposively with the consideration that the agro-industry was still actively producing. The respondents of this research were the owners of the SMS tofu agro-industry. Field research was conducted from August to September 2019. The data collected in this study were primary and secondary data. Then the data analysis method used quantitative descriptive analysis. The results showed that the price of SMS tofu agro-industry production was IDR 1,869.51 per kilogram, the added value of the SMS tofu agro-industry showed a positive value so that it was feasible to be developed, and the SMS tofu agro-industry. is a profitable industry (R / C> 1) because the value of the R / C is more than 1 and feasible.